2020
DOI: 10.21873/anticanres.14097
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcoma of the Chest Wall: A Review of 53 Cases from Two Institutions

Abstract: Background/Aim: Chondrosarcomas (CS) of the chest wall are rare, but present an aggressive biological behavior compared to CS of the extremities. The aims of the present study were to determine factors associated with oncological outcomes as well as complications. Patients and Methods: We retrospectively analyzed 53 patients (42 primary, 11 recurrent tumors). In total, 39 central CS, 10 peripheral CS, 3 dedifferentiated CS and 1 mesenchymal CS were included. The ribs were most commonly affected (68%). Overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…The ribs are thought to be more frequently affected than the sternum, which was also confirmed in our study, as only 12% of the cases were located in sternum 18,21,22 . In accordance with the literature, our results revealed that 60% of the tumors in the ribs were actually locating in the costochondral arches of the sternum 23 .…”
Section: Discussionsupporting
confidence: 92%
“…The ribs are thought to be more frequently affected than the sternum, which was also confirmed in our study, as only 12% of the cases were located in sternum 18,21,22 . In accordance with the literature, our results revealed that 60% of the tumors in the ribs were actually locating in the costochondral arches of the sternum 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Beside that, the seeding of local tissue during resection is theoretically possible. After all, Local recurrence decrease survival rates to 45% at 5 and 10 years compared to 89% and 81% at 5 and 10 years in patients without recurrence [12].…”
Section: Discussionmentioning
confidence: 84%
“…Rascoe et al, reported a local recurrence in 50% of widely excised chondrosarcoma [ 6 ]. In addition to Lenze et al who found that 50% of locally recurrent chondrosarcoma had a clear resection margins [ 12 ]. Moreover, local recurrence increased the risk of distant metastasis ( p = 0.004) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since chest wall reconstruction procedures are developed, wider chest wall resection becomes possible [9]. In this case, the total resection of the costal margin and the six lower ribs didn't offer support of equipment for ribs reconstruction.…”
Section: Discussionmentioning
confidence: 99%